Additional notes on Planchonia brevistipitata kusw. (Lecythidaceae) - Kartawinata, K. (1998)
Planchonia brevistipitata Kkusw. is redescribed and Barringtonia belagaensis P. Chantaranothai is reduced to a synomym of this species